Editorial - Hayes, Grahame (PINS-Psychology in Society, 2026)
The purpose of PINS editorials is to communicate with readers about the material in each issue, and to do this in a way that highlights certain aspects in the articles rather than merely offering summaries. The point of doing this, seeing as many journals don’t have editorials, is to reinforce some of the concerns raised by our authors, and to encourage our readers to think and write about these very concerns. PINS is also aware of the decline of critical thought, in many spheres of society and not just in psychology-related matters, as the new post-apartheid consensus takes hold. Many of the anti-apartheid critiques were exactly that: anti, against, negative. The ideas and practices that prefigured the post-apartheid era during the late1980s were not well formed by the time the demands of the new democratic society were upon us. And now there is a danger within certain circles that "we have arrived" as a country, and hence any critique is interpreted as anti-government, and therefore (non sequitur, by the way) as pro-apartheid! It is a difficult and complex task to shift our critiques from what were predominantly very clear targets - the immorality and barbarism of apartheid as a social order - to the much murkier terrain of the continually and dynamically changing practices, policies, institutions, and laws of millennial South Africa as it tries to transform into a decent and democratic society This is not to deny the range of accomplishments of the post-apartheid government, but this is not the point, for at the same time nobody doubts the extent of the problems facing the transition, and how far we still have to go.